Workload and Coping Strategies Correlated with Burnout Syndrome in Operating Room Nurses - Mohammad Afandi; Sumirah Budi Pertami; Tri Johan Agus Yuswanto; Taufan Arif (STIKes Patria Husada Blitar, 2024)
Operating room nurses are at risk of burnout. They face many stressors, such as the workload that must be finished. Using coping strategies that are adaptive to the situation will allow nurses to cope with their stressors. This research aimed to determine the correlation between workload and coping strategies with burnout syndrome in operating room nurses. The method used correlational research with cross-sectional approach. The population in this study was operating room nurses at Karsa Husada Batu Hospital. The number of samples was 26 nurses based on the total sampling technique. The data was collected from the workload questionnaire, ways of coping questionnaire, and Maslach burnout inventory. The data was analyzed using Spearman rank correlation test. The univariate analysis results showed that most of the respondents had a light workload, 16 people (61.5%), the most of respondents used problem-focus coping, 17 people (65.4%), and most respondents experienced low burnout syndrome, 16 people (61.5%). The bivariate analysis showed that workload had a correlation with burnout syndrome (p = 0.000) and coping strategies had a correlation with burnout syndrome (p = 0.032). A light workload and the use of problem-focused coping will reduce work stress experienced by nurses so that the development of burnout does not occur